ABS composite material and preparation method thereof
By using SAN resin with a high glass transition temperature and a core-shell structure compatibilizer in ABS composite materials, the problems of rapid burning rate and decreased toughness of glass fiber filled ABS materials have been solved, achieving low burning rate and high toughness, making it suitable for products with high fire resistance requirements.
Patent Information
- Application Number
- CN202411543124.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Glass fiber filled ABS composites burn too quickly when heated, failing to meet fire protection requirements. At the same time, the addition of flame retardants leads to a decrease in toughness and processing performance.
Using SAN resin with a high glass transition temperature as the matrix, a core-shell structured silicone-acrylic composite rubber is added as a compatibilizer, along with glass fiber. By controlling the particle size and ratio of the compatibilizer, compatibility and flame retardancy are improved, and wicking effect is suppressed.
It achieves a low burning rate, good toughness and dimensional stability during processing, meets the UL94 flame retardant standard, and is suitable for products with high fire resistance requirements.
Smart Images

Figure BDA0005113215300000071 
Figure BDA0005113215300000072 
Figure BDA0005113215300000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to an ABS composite material and a preparation method and application thereof. Background Art
[0002] ABS (Acrylonitrile-Butadiene-Styrene) material has good processing performance and stability, and most ABS materials currently add a certain amount of glass fiber as filler, which can improve the insulation, high temperature resistance, and fatigue resistance of the product, making the product applicable to a wider range of scenarios. However, due to the wick effect of glass fiber, the burning rate of glass-fiber-filled ABS composite materials when heated is much higher than that of conventional ABS materials, and cannot meet normal fire protection requirements. For this reason, people try to add additional flame retardants, especially halogen flame retardants, to the product for compounding, but this approach is not only environmentally friendly, but also due to the large amount of flame retardants added, the toughness of the product will be significantly reduced, and the performance cannot be taken into account. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present invention is to provide an ABS composite material, which is prepared by compounding a glass fiber reinforcement system by adding a compatibilizer component to a matrix SAN resin with a high glass transition temperature. The product can not only effectively overcome the wick effect of the glass fiber and delay the horizontal burning rate, but also the ABS composite material has higher toughness and processing dimensional stability and is highly practical.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] An ABS composite material comprises the following components in parts by weight:
[0006] 60-85 parts of matrix SAN resin, 10-15 parts of glass fiber, and 15-40 parts of compatibilizer;
[0007] The glass transition temperature of the matrix SAN resin is greater than 105°C;
[0008] The compatibilizer is a core-shell material including a core and an outer shell, wherein the core is an organic silicon-acrylic composite rubber, and the outer shell includes at least one of an MMA resin and a SAN resin;
[0009] The compatibilizer includes a first compatibilizer and a second compatibilizer;
[0010] The average particle size of the first compatibilizer is ≥500nm, and the average particle size of the second compatibilizer is ≤300nm;
[0011] The mass ratio of the first compatibilizer to the second compatibilizer is (2-5):1.
[0012] Further preferably, the mass ratio of the first compatibilizer to the second compatibilizer is in the range of one or any two of 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1.
[0013] Glass fiber reinforced ABS composite materials can take into account both processing stability and toughness in use. However, due to the wick effect of glass fiber, the horizontal combustion rate of such products when heated and burned is extremely high, making the products unable to meet the HB40 requirements of the UL94 flame retardant standard and unable to be used in the preparation of some products that require fire resistance, such as air conditioner fan blades. For this reason, the prior art attempts to add a large amount of flame retardant powder to the ABS resin matrix to inhibit the combustion of the resin matrix, so that the product meets the fire resistance requirements. However, the introduction of flame retardants will not only reduce the toughness of the product, but also lead to a decrease in the dispersion of the product components, which ultimately affects the processing dimensional stability of the product, and it is impossible to take into account both the fire resistance and the use and processing performance of the product. To this end, in the technical solution of the present invention, the inventor uses a SAN resin with a high glass transition temperature as a matrix, and then introduces two silicone rubbers with a core-shell structure as compatibilizers for compounding. The matrix SAN resin with a high glass transition temperature itself has strong dimensional stability due to its cross-linking property, and can achieve good toughness performance after being compounded with glass fiber. At the same time, the two silicone rubbers with graded sizes can not only further improve the toughness of the product, but also serve as dimensional stabilizers, compatibilizers and flame retardants with graded steric hindrance effects. On the one hand, they inhibit the shrinkage of the product caused by resin crystallization during processing, and work together with the matrix SAN resin to achieve high processing dimensional stability. On the other hand, they can improve the compatibility of the matrix SAN resin with glass fiber and the flame retardancy of the overall product, inhibit the wick effect, and reduce the overall horizontal combustion rate of the product.
[0014] However, the ratio of the two compatibilizers of different sizes needs to be controlled, otherwise sufficient steric hindrance and compatibility functions cannot be achieved, and the performance of the product is poor. At the same time, the amount of compatibilizer added cannot be excessive, otherwise due to its water absorption characteristics, the local organic resin and inorganic glass fiber will fit more closely, which will aggravate the wick effect and fail to achieve the purpose of improving fire resistance.
[0015] Preferably, the weight proportion of the matrix SAN resin is 60 to 85 parts, specifically, it can be one or any two of 60, 62, 65, 68, 70, 72, 75, 78, 80, 82, 85 parts.
[0016] Preferably, the weight proportion of the compatibilizer is 15 to 40 parts, specifically, it can be one of or any two of 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, and 40 parts.
[0017] More preferably, the weight proportion of the matrix SAN resin is 68 to 75 parts, and the weight proportion of the compatibilizer is 20 to 30 parts.
[0018] Through the compounding of two key organic resins and glass fiber, the product can achieve better toughness, processing dimensional stability and fire resistance.
[0019] Preferably, in the ABS composite material, the mass percentage of the matrix SAN resin is ≥50%.
[0020] Preferably, the density of the matrix SAN resin tested according to ISO 1183-1-2019 method A is 1 to 1.1 g / cm 3 .
[0021] Preferably, the glass transition temperature of the matrix SAN resin is 106-112°C, more preferably 107-110°C.
[0022] The glass transition temperature of the matrix SAN resin of the present invention is the glass transition temperature Tg.
[0023] More preferably, the glass transition temperature of the matrix SAN resin is confirmed by DSC method according to ISO 11357-2-1999 Plastics Differential Scanning Calorimetry (DSC) Part 2, with a heating rate of 10°C / min, nitrogen atmosphere, atmosphere flow rate of 50 mL / min, room temperature to 150°C, and instrument model DSC300A.
[0024] Preferably, the shell of the compatibilizer is MMA resin.
[0025] The outer shell layer of MMA (methyl methacrylate) resin and SAN resin as the compatibilizer has high compatibility with the matrix SAN resin of the present invention and can be well dispersed in the matrix resin, so that the product can achieve better mechanical toughness and dimensional stability.
[0026] More preferably, the silicon content of the compatibilizer is 10-40 wt%.
[0027] More preferably, the silicon content of the compatibilizer is 20-38 wt %.
[0028] More preferably, the average particle size of the first compatibilizer in the compatibilizer is 550-700 nm.
[0029] More preferably, the average particle size of the first compatibilizer is in the range of one or any two of 550 nm, 580 nm, 600 nm, 620 nm, 650 nm, 680 nm, and 700 nm.
[0030] More preferably, the average thickness of the shell of the first compatibilizer is 50-200 nm.
[0031] More preferably, the average particle size of the second compatibilizer in the compatibilizer is 50 to 280 nm.
[0032] More preferably, the average particle size of the second compatibilizer in the compatibilizer is in the range of one or any two of 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, and 280 nm.
[0033] More preferably, the average thickness of the shell of the second compatibilizer is 10-100 nm.
[0034] The silicon content of the compatibilizer of the present invention, the average particle size of the two compatibilizers and the average shell thickness are confirmed by the following method: the compatibilizer is observed under 100 kV by a JEM-1011 transmission electron microscope, and then the silicon content of the compatibilizer is confirmed by an EDS elemental analysis method; the specific method is: the compatibilizer is cut and crushed into powder after being frozen in liquid nitrogen, and then loaded on a sample-carrying copper mesh, pressed into tablets, steam-dyed, and a mapping software is used to distinguish the first compatibilizer from the second compatibilizer, and then 30 particles of the first compatibilizer and 30 particles of the second compatibilizer are screened for particle size test, and the average value is calculated to obtain the average particle size of the first compatibilizer and the second compatibilizer; then the magnification is adjusted, and the thickness of the shell of the above-screened particles is confirmed by a mapping software, and the average value is calculated to obtain the average thickness of the shell of the first compatibilizer and the second compatibilizer.
[0035] Preferably, the glass fibers have an average length of 2 to 4 mm and an average diameter of 10 to 15 μm.
[0036] Further preferably, the glass fiber can be commercially available types such as HMG436S-10-4.0 produced by Taishan Glass, ECS13-4.5-508A, ECS13-03-534A, ECS13-4.5-560A produced by Jushi Fiberglass, or other existing products, without particular limitation.
[0037] Preferably, the ABS composite material further comprises 0.8 to 3 parts of functional additives;
[0038] Further preferably, the functional additives include but are not limited to at least one of an antistatic agent, a lubricant, a hydrolysis resistance agent, an antioxidant, an anti-ultraviolet agent, and a colorant. Those skilled in the art may add various functional additives according to actual needs without affecting the expected performance of the ABS composite material of the present invention. For example, in order to make the ABS composite material have antioxidant properties during application, those skilled in the art may add an antioxidant to the product; in order to make the ABS composite material easier to demold during processing, those skilled in the art may add a lubricant to the product.
[0039] More preferably, the ABS composite material further comprises 0.5 to 2 parts of lubricant and / or 0.3 to 1 parts of antioxidant.
[0040] More preferably, the antioxidant is at least one of a hindered phenol antioxidant, a hindered amine antioxidant, and a phosphite antioxidant.
[0041] More preferably, the lubricant is at least one of an amide lubricant and a polyethylene wax lubricant.
[0042] Another object of the present invention is to provide a method for preparing the ABS composite material, comprising the following steps:
[0043] The components are added into a screw extruder for melt extrusion and granulation to obtain the ABS composite material.
[0044] Preferably, the temperature zones of the screw extruder are set to 200-210°C in zone 1, 200-210°C in zone 2, 210-220°C in zone 3, 210-220°C in zone 4, 210-220°C in zone 5, 220-230°C in zone 6, 220-230°C in zone 7, 230-240°C in zone 8, 230-240°C in zone 9, and 230-240°C in zone 10, the screw speed is 450-550rpm, and the screw aspect ratio is (40-60):1.
[0045] Another object of the present invention is to provide application of the ABS composite material in the preparation of air-conditioning parts.
[0046] Preferably, the air conditioning components include air conditioning axial flow fan blades and air conditioning perfusion fan blades.
[0047] The ABS composite material of the present invention is based on the special selection of two organic resins, so that it can still achieve a low horizontal combustion rate under a glass system, has good fire resistance, and has high toughness and processing dimensional stability. It is very suitable for application scenarios such as air-conditioning parts that require high fire resistance, usage mechanics, and usage stability.
[0048] Another object of the present invention is to provide an air-conditioning component, comprising the ABS composite material of the present invention.
[0049] The beneficial effect of the present invention is that the present invention provides an ABS composite material, and a glass fiber reinforcement system is prepared by compounding a compatibilizer component into a matrix SAN resin with a high glass transition temperature. The product can not only effectively overcome the wick effect of the glass fiber and delay the horizontal burning rate, but also the ABS composite material has higher toughness and processing dimensional stability and is highly practical. DETAILED DESCRIPTION
[0050] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0051] Examples 1 to 15
[0052] An embodiment of an ABS composite material and a preparation method and application thereof according to the present invention, the components of the ABS composite material are shown in Table 1.
[0053] The preparation method of the ABS composite material comprises the following steps:
[0054] The components are mixed uniformly, and then melt-extruded and granulated in a twin-screw extruder to obtain the ABS composite material.
[0055] When the components are melt-extruded, the temperature zones of the twin-screw extruder are set to 200°C for zone 1, 210°C for zone 2, 210°C for zone 3, 210°C for zone 4, 220°C for zone 5, 220°C for zone 6, 230°C for zone 7, 230°C for zone 8, 240°C for zone 9, and 240°C for zone 10, the screw speed is 500rpm, and the screw aspect ratio is 48:1.
[0056] Comparative Examples 1 to 7
[0057] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.
[0058] Among the components described in each embodiment and comparative example,
[0059] The matrix SAN resin 1 is DXG05 produced by Zhejiang Suqi New Materials Co., Ltd., and has a glass transition temperature of 110°C;
[0060] The matrix SAN resin 2 is DXG04 produced by Zhejiang Suqi New Materials Co., Ltd., and has a glass transition temperature of 107°C;
[0061] The matrix SAN resin 3 is KFA-130 produced by Liaoning Jinfa, and has a glass transition temperature of 105°C;
[0062] The compatibilizer 1 is S-2100 produced by Mitsubishi of Japan, which includes a core and a shell from the inside to the outside, the shell is MMA resin, the core is organic silicon-acrylic composite rubber, the average particle size is 600nm, the average thickness of the shell is 180nm, and the silicon content is 26wt%;
[0063] The compatibilizer 2 is S-2130 produced by Mitsubishi of Japan, which includes a core and a shell from the inside to the outside, the shell is MMA resin, the core is organic silicon-acrylic composite rubber, the average particle size is 600nm, the average thickness of the shell is 200nm, and the silicon content is 30wt%;
[0064] The compatibilizer 3 is S-2030 produced by Mitsubishi of Japan, which includes a core and a shell from the inside to the outside, the shell is MMA resin, the core is organic silicon-acrylic composite rubber, the average particle size is 200nm, the average thickness of the shell is 50nm, and the silicon content is 30wt%;
[0065] The compatibilizer 4 is SX-005 produced by Mitsubishi of Japan, which includes a core and a shell from the inside to the outside, the shell is MMA resin, the core is organic silicon-acrylic composite rubber, the average particle size is 200nm, the average thickness of the shell is 60nm, and the silicon content is 35wt%;
[0066] The compatibilizer 5 is SRK-200A produced by Mitsubishi of Japan, which includes a core and a shell from the inside to the outside, the shell is SAN resin, the core is organic silicon-acrylic composite rubber, the average particle size is 200nm, the average thickness of the shell is 50nm, and the silicon content is 30wt%;
[0067] The compatibilizer 6 is S-2001 produced by Mitsubishi of Japan, and includes a core and a shell from the inside to the outside. The shell is MMA resin, the core is organic silicon-acrylic composite rubber, the average particle size is 200nm, the average thickness of the shell is 55nm, and the silicon content is 18wt%;
[0068] The compatibilizer 7 is SX-006 produced by Mitsubishi of Japan, which includes a core and a shell from the inside to the outside, the shell is SAN resin, the core is organic silicon-acrylic composite rubber, the average particle size is 60nm, the average thickness of the shell is 20nm, and the silicon content is 18wt%;
[0069] The acrylic rubber is W450A produced by Mitsubishi of Japan, and includes a core and an outer shell from the inside to the outside. The outer shell is SAN resin, the core is acrylic rubber, the average particle size is 500nm, and the average thickness of the outer shell is 200nm;
[0070] The glass fiber is HMG436S-10-4.0 produced by Taishan Glass, with an average length of 4 mm and an average diameter of 10 μm;
[0071] The lubricant is an amide lubricant produced in Indonesia, EBS B50, ethylene bis stearamide;
[0072] The antioxidant is Y-001 produced by BASF, a hindered phenol antioxidant, pentaerythritol tetrakis[β(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0073] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0074] Table 1
[0075]
[0076] Table 2
[0077]
[0078] In order to verify the performance of the ABS composite material of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0079] (1) Izod notched impact strength test: tested according to ISO 180-2023, type A notch, pendulum energy 2.75 J.
[0080] (2) Horizontal burning rate test: HB40 test according to UL94-2020, sample thickness 3.0 mm;
[0081] (3) Processing dimensional stability test: According to GB / T 15585-1995, the cross shrinkage test method is used to test the indicators in the direction parallel to the material flow.
[0082] The test results are shown in Tables 3 and 4.
[0083] Table 3
[0084]
[0085] Table 4
[0086]
[0087] It can be seen from Table 3 and Table 4 that the ABS composite material of the present invention has ideal comprehensive properties, and the cantilever beam notched impact strength of the products of each embodiment can reach 8KJ / m 2and above, the horizontal burning rate meets the HB40 requirement, that is, the horizontal burning rate is not higher than 40 mm / min, and the processing dimensional stability is high, and the cross shrinkage rate is less than 3‰. It can be seen from Examples 1 to 4 that the performance of the product under different ratios of two different compatibilizer particles varies. In the range of (2 to 5): 1, the product can take into account good impact strength, fire resistance and dimensional stability. In contrast, the ratio of the two in Comparative Examples 2 and 3 does not meet the requirements of the present invention, the impact strength of the product decreases, and the horizontal burning rate does not meet the HB40 requirement. It can be seen from Example 2, Example 5 and Comparative Examples 4 and 5 that in the product, the addition ratio of the base SAN resin and the compatibilizer not only has a significant effect on the impact strength of the product, but also has an effect on the fire resistance and dimensional stability. When the content of the base SAN resin is too little, the fire resistance and dimensional stability of the product are poor. As the proportion of this component increases, the horizontal combustion rate of the product decreases and the dimensional stability improves. However, when the proportion of this component is too large, not only the impact strength of the product is low, but also the probability of the occurrence of the "wick effect" is increased again, and the fire resistance becomes poor.
[0088] In the product of comparative example 1, the base SAN resin used is not of the type with high glass transition temperature. In addition to the possibility of failing to guarantee mechanical properties, the fire retardant performance of the product also cannot achieve the same effect as the product of the embodiment. The main reason is that this type of conventional SAN resin cannot achieve the ideal cross-linking effect and compatibility, and the degree of "wick effect" of glass fiber is very serious; in the product of comparative example 6, the compounded resin used is not a graded composite silicone rubber, but a compound of acrylic rubber and silicone rubber with similar structure. It can be seen that although the product has good dimensional stability when used as a compatibilizer, the fire retardant performance cannot meet the standard, and the impact strength is low, which cannot meet the use standard at all. According to Examples 2, 9 and 10 to 15, it can be seen that when the compatibilizer particles of graded sizes are used for matching, the product can achieve good comprehensive performance, among which when the shell of the compatibilizer selects MMA resin and the silicon content reaches more than 20wt%, the comprehensive performance of the prepared product is better.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An ABS composite material, characterized in that: The composition comprises the following components in parts by weight: 60-85 parts of matrix SAN resin, 10-15 parts of glass fiber, and 15-40 parts of compatibilizer; The glass transition temperature of the matrix SAN resin is greater than 105°C; The compatibilizer is a core-shell material including a core and an outer shell, wherein the core is an organic silicon-acrylic composite rubber, and the outer shell includes at least one of an MMA resin and a SAN resin; The compatibilizer includes a first compatibilizer and a second compatibilizer; The average particle size of the first compatibilizer is ≥500nm, and the average particle size of the second compatibilizer is ≤300nm; The mass ratio of the first compatibilizer to the second compatibilizer is (2-5):
1.
2. The ABS composite material according to claim 1, characterized in that: The glass transition temperature of the matrix SAN resin is 106-112°C.
3. The ABS composite material according to claim 1, characterized in that: The average particle size of the first compatibilizer in the compatibilizer is 550-700 nm; the average particle size of the second compatibilizer in the compatibilizer is 50-280 nm.
4. The ABS composite material according to claim 1, characterized in that: The average shell thickness of the first compatibilizer is 50-200 nm; the average shell thickness of the second compatibilizer is 10-100 nm.
5. The ABS composite material according to claim 1, characterized in that: The silicon content of the compatibilizer is 10-40 wt %.
6. The ABS composite material according to claim 1, characterized in that: The ABS composite material further includes 0.8 to 3 parts of functional additives; preferably, the ABS composite material further includes 0.5 to 2 parts of lubricants and / or 0.3 to 1 parts of antioxidants.
7. The method for preparing the ABS composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components are added into a screw extruder for melt extrusion and granulation to obtain the ABS composite material.
8. Use of the ABS composite material according to any one of claims 1 to 6 in the preparation of air-conditioning parts.
9. The use according to claim 8, characterized in that The air conditioning components include air conditioning axial flow fan blades and air conditioning perfusion fan blades.
10. An air conditioning component, characterized in that: The invention comprises the ABS composite material as claimed in any one of claims 1 to 6.
Citation Information
Patent Citations
Glass fiber reinforced PBT composite material and preparation method thereof
CN114656759A
PA / PPE composite material and preparation method and application thereof
CN117700985A
High-dispersion glass fiber, glass fiber reinforced nylon material, preparation method therefor and application thereof
WO2023011205A1